Knowledge spillovers, transboundary pollution, and growth. - Alemdar, Nedim M.; Özyildirim, Süheyla (Oxford Economic Papers, 2002)
Trade in natural resources is construed as a dynamic game between North and South. Policies that promote growth in the North also cause knowledge spillovers and transboundary pollution in the South. Cooperative and noncooperative Nash equilibria of this strategic trade game are simulated under various scenarios by parallel genetic algorithms to highlight the distortions in the growth/pollution trade-off. Absent cooperation, both regions benefit when North simultaneously cuts waste and increases knowledge spillovers, impelling South to reciprocate by lower resource prices. Reprinted by permission of the publisher.